PENERAPAN PENCATATAN LAPORAN KEUANGAN SEDERHANA TERHADAP UMKM SURABAYA: (Studi Kasus pada CV. Zinergy Indonesia) - Septianis Savita; Agus Subandoro (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study aims to determine the application of recording simple financial statements on CV. Zincergy Indonesia. Sampling is done by taking transaction data in CV. Zinergy Indonesia during the period April 2022. This research is a qualitative research by comparing the process of recording financial statements on CV. Zinergy Indonesia on a daily basis that does not meet the criteria for good recording with a simple process of recording financial statements by researchers. The results of the study showed that CV. Zinergy Indonesia suffered an unknown loss due to irregular financial reporting.